BOOK2U@libpsp - Ismail, Zamzilah; Yahya, Rosriani; Md Ariff, Nor Abidah; Sulaiman, Rozihan; Ismail, Nuraini (Universiti Teknologi MARA, Kedah, 2017)
Keeping with the latest trends and technologies, Library PSP has introduced new innovation in circulation services, “Drive-Thru Book Check Out” to borrow materials and “Book Return QR Code” to return borrowed materials to a box without parking first. “Drive-Thru Book Check Out” service is an initiative to support the Door-to Door program. This program allows patrons who are unable to come to the library in person to borrow the library materials. Patrons interested in this service can fill up online borrowing form and pick up the books through “Drive Thru” counter. Besides, “Book Return QR code” links to the Library Management System KOHA. After scanning the QR Code, users are directed to a mobile optimized website that provides information of returning the books. The web check-in designed and developed for Android and IOS. The library members may install QR Code Scanner and can start using it with zero cost, access at unlimited time and easy to use. It also can improve the circulation statistics and reduce fine. Furthermore, this web check-in is one of the initiatives to support PSP’s POLYGREEN program in reducing electricity usage and achieving Ekosistem Kondusif Sektor Awam (EKSA) certificate, by implementing 3R (Reduce, reuse and recycle) concept.